Psycho-social Determinants of Employee Green Behavior among IT Professionals - George, Jovita Sherin; Jayakumar, K.N.; Jose, Amal Tom (Makara Human Behavior Studies in Asia, 2024)
As environmental degradation and hazards caused by the information technology (IT) industry reach critical levels, promoting pro-environmental behaviors within IT firms is crucial. These behaviors not only reduce operational costs but also enhance employee productivity. The primary objective of this study is to assess the roles of consideration of future consequences (CFC), nature relatedness (NR), and organizational commitment (OC) as determinants of employee green behavior (EGB). Results revealed a significant relationship between CFC and EGB. Specifically, CFC-Future has a significant positive relationship with EGB, whereas CFC-Immediate has a significant negative correlation with EGB. Additionally, the relationship between EGB and NR is significant and positive. A significant positive correlation is also observed between EGB and OC. Furthermore, regression analysis of the psychological variables revealed that these factors collectively explain 29% of the variance in EGB, with contributions from CFC-Future, NR-6, and continuance OC.